2018
DOI: 10.1177/1362361318766571
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Big Five personality traits in autism spectrum disorder

Abstract: The present meta-analysis synthesizes the emerging literature on the relationship of Big Five personality traits to autism spectrum disorder. Studies were included if they (1) either (a) measured autism spectrum disorder characteristics using a metric that yielded a single score quantification of the magnitude of autism spectrum disorder characteristics and/or (b) studied individuals with an autism spectrum disorder diagnosis compared to individuals without an autism spectrum disorder diagnosis and (2) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 74 publications
8
49
1
Order By: Relevance
“…For instance, it could indicate a high memory performance, a high attention to colours, or a high degree of conscientiousness. The latter possibility, however, would not account for the relation between the degree of synaesthesia and autistic traits that we found, as a recent meta-analysis (Lodi-Smith et al 2018) found conscientiousness to be negatively correlation with ASD characteristics. This limitation concerns the widely discussed debate whether synaesthesia should be considered as a continuous traits or all-or-none phenomenon, as discussed in the introduction.…”
Section: Strengths and Limitations Of The Present Studycontrasting
confidence: 63%
“…For instance, it could indicate a high memory performance, a high attention to colours, or a high degree of conscientiousness. The latter possibility, however, would not account for the relation between the degree of synaesthesia and autistic traits that we found, as a recent meta-analysis (Lodi-Smith et al 2018) found conscientiousness to be negatively correlation with ASD characteristics. This limitation concerns the widely discussed debate whether synaesthesia should be considered as a continuous traits or all-or-none phenomenon, as discussed in the introduction.…”
Section: Strengths and Limitations Of The Present Studycontrasting
confidence: 63%
“…The correlations of the Big Five personality traits with the total RAADS-14 Rus score, taken as a general measure of autistic traits, were highly consistent with the earlier findings [41], revealing moderate positive correlations with Neuroticism, moderate negative correlation with Extraversion, and weaker negative correlations with Agreeableness, Openness to experience, and Conscientiousness, similarly to a study using RAADS-R and IPIP-NEO-120 [42]. These results support good discriminative validity of the RAADS-14 Rus and confirm our prediction that the character of the relation between autistic traits, as measured by the RAADS-14 Rus, and the Big Five personality traits for the Russian sample is similar to such relation for other national populations.…”
Section: Age and Gender Differencessupporting
confidence: 89%
“…There are numerous studies exploring the links between the autism traits and other personality factors and constructs. The Big Five personality model is probably the most well-established general personality construct [24] which was found to strongly relate to the autism traits in a large number of studies, consistently revealing moderate positive correlations of ASD scores to neuroticism, and weak to moderate negative correlations to all the other Big Five factors [25]. A study utilizing multivariate approaches to explore the relations between IPIP-NEO-120 and RAADS-R scores found that Big Five personality factors accounted for 70 % of variance in autism trait scores [26].…”
Section: Assessing Autistic Traits In Adult Population In Russia: Curmentioning
confidence: 99%
“…ASD and SZ share elevated levels of schizotypal personality traits and neuroticism, which go along with difficulties in social life. In healthy subjects, these traits increase the risk for the disorders independent of other risks [10][11][12][13] and they are dimensionally distributed among healthy subjects and patients [14]. It is yet unknown, whether APA leads to neuroticism or schizotypy in the offspring, and if so, what the underlying mechanisms are.…”
Section: Introductionmentioning
confidence: 99%